Synthesis of novel 3,4-dihydroquinoxalin-2(1H)-one derivatives - Shabaan, Mohammed; Taher, Azza Taher; Osman, Eman Omar (European Journal of Chemistry, 2011)
New derivatives of 3,4-dihydroquinoxaline-2(1H)-one were synthesized and characterized. Representative examples were evaluated for their antimicrobial and antifungal activities using Tetracycline and Nystatin as reference compound. One of the tested compounds 10a was found to exhibit slight activity against Staphylococcus aureus. Compounds 10b, 11b and 14b showed slight activity against Escherichia coli. Moreover, nineteen compounds were screened for their inhibition effect on CDK5, CK1, and GSK-3β. None of the tested compounds showed an inhibition activity below 10 µM concentration.